2010
DOI: 10.1007/s12022-010-9114-y
|View full text |Cite
|
Sign up to set email alerts
|

Universal Markers of Thyroid Malignancies: Galectin-3, HBME-1, and Cytokeratin-19

Abstract: Difficulties in diagnosis of thyroid lesions, even with histologic analysis, are well known. This study has been carried on to evaluate the role of immunohistochemical markers including galectin-3, Hector Battifora mesothelial cell-1 (HBME-1), and cytokeratin-19 in the diagnosis and differential diagnosis of benign and malignant thyroid lesions. The expressions of galectin-3, HBME-1, and cytokeratin-19 were tested in formalin-fixed, paraffin-embedded tissues from 458 surgically resected thyroid lesions includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 33 publications
5
45
0
1
Order By: Relevance
“…In our study, these ratios were respectively 83.3% and 60% for distinguishing FND-FA and PTC, and 70% and 60% for distinguishing FND-FA and FVPTC. In agreement with the literature [4,8], we observed that usage of CK19 by itself had the highest sensitivity as a marker in distinguishing benign lesions from PTC and FVPTC (83.3%, 70%). However, its specificity was lower due to its positivity in benign lesions (60%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, these ratios were respectively 83.3% and 60% for distinguishing FND-FA and PTC, and 70% and 60% for distinguishing FND-FA and FVPTC. In agreement with the literature [4,8], we observed that usage of CK19 by itself had the highest sensitivity as a marker in distinguishing benign lesions from PTC and FVPTC (83.3%, 70%). However, its specificity was lower due to its positivity in benign lesions (60%).…”
Section: Discussionsupporting
confidence: 92%
“…CK19 is a low molecular weight cytokeratin which is expressed in various epithelial tissues and tumors [10]. While there are differences among studies in terms of the extensiveness and intensity of its expression in follicular epithelial cell derived lesions of the thyroid, it is more diffused and stronger in papillary carcinoma [5,8,9,10]. Additionally, it is known to be positively stained also in benign nodules and follicular adenoma [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies showed that the expression level of CK19 or CK19 fragments differ in various subtypes of thyroid tumors (Raphael et al 1994, Miettinen et al 1997. Most studies demonstrated that overexpression of CK19 is mainly related to papillary thyroid cancer with a positive rate, accounting for 70-100% of all cancers (Flanagan et al 2008, Krzeslak et al 2008, Barut et al 2010, Gong et al 2012. Furthermore, CK19 has been used in combination with PAX8 and HBME1 to increase the specificity of diagnosis for thyroid tumors by FNA (Schmitt et al 2010, Cochand-Priollet et al 2011.…”
Section: Endocrine-related Cancermentioning
confidence: 99%